Measurement of a True V˙O2max during a Ramp Incremental Test Is Not Confirmed by a Verification Phase - Murias, Juan M.; Pogliaghi, Silvia; Paterson, Donald H. (Frontiers in Physiology, 2018)
The accuracy of an exhaustive ramp incremental (RI) test to determine maximal oxygen uptake (V̇O2max) was recently questioned and the utilization of a verification phase proposed as a gold standard. This study compared the oxygen uptake (V̇O2) during a RI test to that obtained during a verification phase aimed to confirm attainment of V̇O2max. Sixty-one healthy males (31 older (O) 65±5 yrs.; 30 younger (Y) 25±4 yrs.) performed a RI test (15-20 W/min for O and 25 W/min for Y). At the end of the RI test, a 5-min recovery period was followed by a verification phase of constant load cycling to fatigue at either 85% (n= 16) or 105% (n= 45) of the peak power output obtained from the RI test. The highest V̇O2 after the RI test (39.8±11.5 mL∙kg-1∙min-1) and the verification phase (40.1±11.2 mL∙kg-1∙min-1) were not different (p=0.33) and they were highly correlated (r=0.99; p<0.01). This response was not affected by age or intensity of the verification phase. The Bland-Altman analysis revealed a very small absolute bias (-0.25 mL∙kg-1∙min-1, not different from 0) and a precision of ±1.56 mL∙kg-1∙min-1 between measures. This study indicated that a verification phase does not highlight an under-estimation of V̇O2max derived from a RI test, in a large and heterogeneous group of healthy younger and older men naïve to laboratory testing procedures. Moreover, only minor within-individual differences were observed between the maximal V̇O2 elicited during the RI and the verification phase. Thus a verification phase does not add any validation of the determination of a V̇O2max. Therefore, the recommendation that a verification phase should become a gold standard procedure, although initially appealing, is not supported by the experimental data.